The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1590/s0100-46702002000200031
|View full text |Cite
|
Sign up to set email alerts
|

Redução de crômio hexavalente por substâncias húmicas aquáticas imobilizadas em aminopropil sílica

Abstract: Estudou-se a redução de Cr(VI) à Cr(III) utilizando-se um novo suporte preparado pela ativação de aminopropil sílica com substâncias húmicas aquáticas (ATPS-SiO2-SHA). Coletaram-se amostras de água no Corrégo Itapitangui localizado no município de Cananéia-SP e extraíram-se as SHA utilizando-se procedimento recomendado pela Sociedade Internacional de Substâncias Húmicas. Após purificação por diálise, fez-se a imobilização das SHA na aminopropil sílica (APTS-SiO2) em pH 7,0, sob agitação mecânica por 48 horas à… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…For the first case AHS could reduce Cr(VI) to Cr(III) form and subsequently complex the reduced form. Romão et al 50 demonstrated that AHS can reduce Cr(VI) in acid pH (2.5), being that this behavior was not observed for pH 6.0. Probably this mechanism can be disregarded for this work.…”
Section: Fluorescence Spectramentioning
confidence: 99%
“…For the first case AHS could reduce Cr(VI) to Cr(III) form and subsequently complex the reduced form. Romão et al 50 demonstrated that AHS can reduce Cr(VI) in acid pH (2.5), being that this behavior was not observed for pH 6.0. Probably this mechanism can be disregarded for this work.…”
Section: Fluorescence Spectramentioning
confidence: 99%